The effect of material non-linearity on the predicted performance of road pavement - Aman, Mohamad Yusri (2003)
TIle purpose of this study is to determine the effect of non-linearity of unbound granular material as base course on the road pavement. This study focused in the determination of the effect of density and level of stress on resilient modulus at granular base material under repeated loading. The granular material was compacted at optimum moisture content of the 90 %, 95 % and 100 % of maximum dry density. The stress application assign to the stress situation caused by wheel loading affected at the base, upper subbase and lower subbase layer pavement. From the test result, the graph was plotted by regression analysis and the model fitted base on Brown and PeII, 1976, as Mr = kl (9/90)k2. The result obtained was analysed by Analysis of Variant (ANOVA) using t-test to detennine the effect of resilient modulus on density and level of stress. The resilient modulus increases as the level of stress and density increase, which means that the resilient modulus of unbound granular material is stress dependent and the relationship is non-linear. The effect of non-linear unbound granular material on the road pavement is determined by MICH-PA VE software. The flexible pavement was analysed based on Manual of Pavement Design (JKR) which the standard and construction layer thickness was taken. The analyses consist of the maximum horizontal tensile and the average compressive strains in asphalt layer and compressive strain at the top sub grade. These strains are related to the fatigue life and rut depth of asphalt pavement. TIle resilient modulus increases with the increase in density. Everything being equal pavement with unbound layer with lower may have a higher horizontal or radial strain at the bottom of asphalt, and therefore will have shorter fatigue life. The lower density at the unbound layer tends to increase the average compressive strain within the asphalt layer and compressive strain at the top of subgrade, which may cause at the increment rate total plastic defonnation at the pavement.